PENINGKATAN KEAFTIFAN BELAJAR PESERTA DIDIK MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA PESERTA DIDIK KELAS 4 DI SDN 096 SARIJADI SELATAN - Ega Hidayat; Ghullam Hamdu; Eva Riyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Student active learning is all forms of activities carried out by students during the learning process involving cognitive, affective, and psychomotor aspects. The active learning of these students will affect the learning outcomes to be achieved. However, the active learning of students, in general, is still low. Therefore, the researcher chose the PBL learning model to overcome this problem, which is based on the literature studies that have been conducted. In addition to students getting hands-on experience, teachers can also find out students' level of active learning. The PBL learning model aims to increase student learning activity. The formulation of the problem in this study, in general, is how to increase students' active learning through the PBL model in elementary schools, while the purpose of this research is to describe the increase in student learning activeness through the PBL model in elementary schools. The research was conducted at SD Negeri 096 Sarijadi Selatan Bandung City using Classroom Action Research (PTK), which comprised 68% of the first cycle and 96% of the second cycle; there was an increase involving fourth-grade students as research subjects. Data collection techniques used are observation and questionnaires. Based on the data obtained and the findings, it was concluded that elementary school students learning activeness increased after learning using the PBL model